Case Report of Focal Epithelial Hyperplasia (Heck's Disease) with Polymerase Chain Reaction Detection of Human Papillomavirus 13. Issue 3 (13th April 2016) - Brehm, Mary A.; Gordon, Katie; Firan, Miahil; Rady, Peter; Agim, Nnenna
Abstract: Focal epithelial hyperplasia (FEH), or Heck's disease, is an uncommon benign proliferation of oral mucosa caused by the human papillomavirus (HPV), particularly subtypes 13 and 32. The disease typically presents in young Native American patients and is characterized by multiple asymptomatic papules and nodules on the oral mucosa, lips, tongue, and gingiva. The factors that determine susceptibility to FEH are unknown, but the ethnic and geographic distribution of FEH suggests that genetic predisposition, particularly having the human lymphocytic antigen DR4 type, may be involved in pathogenesis. We report a case of FEH with polymerase chain reaction detection of HPV13 in a healthy 11‐year‐old Hispanic girl and discuss the current understanding of disease pathogenesis, susceptibility, and treatment.